THE EVALUATION OF IMPLEMENTING ONLINE LEARNING AT UNIMED FACULTY OF ENGINEERING - Zulkifli Matondang; Sarwa Sarwa; Liana Atika; Sutrisno Sutrisno (LPPM Universitas Negeri Jakarta, 2021)
This research aims to evaluate the online learning implementation activities at the UNIMED Faculty of Engineering to determine the various weaknesses and constraints. The research approach used is the CIPP model of Stufflebeam. And it focused on the content/material, facilities, processes, and outputs of online learning. Data were obtained from UNIMED Faculty of Engineering students through online questionnaires. The results showed that 1) the availability of learning resources is still low, as a content aspect, 2) network strength is weak at the input aspect, 3) the helpdesk service is lacking at the process aspect, and 4) the online effectiveness is low at the product aspect. On average, out of these four components, the lowest is online learning tools. In conclusion, this research found that learning facilities contributed to online learning effectiveness at the UNIMED Faculty of Engineering.